Renewed tectonic extrusion of high-grade metamorphic rocks in the MCT footwall since Late Miocene (Sutlej Valley, India) - Baudraz, Vincent; Vannay, Jean-Claude; Catlos, Elizabeth; Cosca, Mike; Vennemann, Torsten (Himalayan Journal of Sciences, 2008)
Himalayan Journal of Sciences Vol.2(4) Special Issue 2004 pp. 102-3